1994
DOI: 10.1159/000244074
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Umbilical Cord Serum Levels of Inhibin, Testosterone, Oestradiol Dehydroepiandrosterone Sulphate, and Sex Hormone-Binding Globulin in Human Term Neonates

Abstract: The contribution of the fetus to inhibin production in human pregnancy is unclear. Previous studies have reported inhibin concentrations in cord blood but on limited sample numbers. The present study is a more extensive examination of sex differences in immunoreactive inhibin and steroidal hormones in term umbilical cord blood. Venous serum concentrations of inhibin were found to be significantly higher in males (mean ± SD 2,168 ± 914 pg/ml, n = 62) than in females (1,761 ± 951 pg/ml, n = 63) (p < 0.01). Male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 23 publications
6
34
1
1
Order By: Relevance
“…Whether birth size is associated with maternal estradiol, however, is unclear (38,(41)(42)(43). In the cord, birth weight is not associated with estradiol (38,42,44,45), estrone (38,44), or androgens (38,45), and the association with estriol is unclear (38,42). Overall, the data imply that birth weight is positively associated with maternal but not fetal estrogen concentrations.…”
Section: Prominent Hypotheses To Explain Prenatal Risk Factorsmentioning
confidence: 84%
See 1 more Smart Citation
“…Whether birth size is associated with maternal estradiol, however, is unclear (38,(41)(42)(43). In the cord, birth weight is not associated with estradiol (38,42,44,45), estrone (38,44), or androgens (38,45), and the association with estriol is unclear (38,42). Overall, the data imply that birth weight is positively associated with maternal but not fetal estrogen concentrations.…”
Section: Prominent Hypotheses To Explain Prenatal Risk Factorsmentioning
confidence: 84%
“…One study showed no association with DHEA, DHEA sulfate, androstenedione, and testosterone measured at the end of pregnancy (38); however, another larger study found higher maternal testosterone levels at weeks 17 and 33 in the lower-birthweight babies (65). In the cord, birth weight was not associated with androgens in two studies (38,45). Thus, there is little evidence that birth weight is positively correlated with maternal or cord androgens, although additional studies are necessary.…”
Section: Prominent Hypotheses To Explain Prenatal Risk Factorsmentioning
confidence: 99%
“…Our data show no association of birth weight with first trimester estrogens seeming to suggest that if oestrogen explains the association of birth weight and breast cancer risk, the critical exposure window may be later in pregnancy. Yet associations of birth weight with cord estrogens are unclear (Simmons et al, 1994;Shibata et al, 2002;Troisi et al, 2003;Nagata et al, 2006), and breast cancer risk in women prenatally exposed to diethylstilbestrol does not differ by trimester of first exposure (Palmer et al, 2006). Other prenatal factors could act differently.…”
Section: Discussionmentioning
confidence: 99%
“…Because testosterone is the natural substrate in estrogen biosynthesis and the responsible enzyme (CYP19͞aromatase) is expressed by the prostate (10), it is plausible that estrogen can be produced locally within the prostatic tissue in the newborn period. Second, in late prenatal and early postnatal boys, circulating levels of estrogen are high, reaching equal or higher levels than in girls (8). Third, in the present and previous work (2,11), it was demonstrated that the steroid 5␣-androstane-3␤, 17␤-diol (3␤ A-diol), a metabolite of dihydrotestosterone (DHT) with estrogenic properties, could serve as a mitogen in the prostate in the neonatal period acting through ER␣.…”
Section: Estrogen Exposure To Perinatal Boysmentioning
confidence: 64%
“…Interestingly, several such ways of exposure seem to exist. First, infant boys show physiologically high levels of testosterone because of a postnatal reproductive hormone surge at the age of 1-3 months, sometimes referred to as ''baby puberty'' (8,9). Because testosterone is the natural substrate in estrogen biosynthesis and the responsible enzyme (CYP19͞aromatase) is expressed by the prostate (10), it is plausible that estrogen can be produced locally within the prostatic tissue in the newborn period.…”
Section: Estrogen Exposure To Perinatal Boysmentioning
confidence: 99%